Neo-traditionalism as a factor of neoconservative modernization: specificity of the evolution of power and control - Valentin Tyan (Управление)
The article deals with the problem of neotraditionalism (including Russian) on the modern empirical basis. The author of the study considers, that neotraditionalism as a factor of neoconservative modernization is dual and irrational. Since the continuity of political traditions is important for the development of the state, the continuation of good traditions is the ethical basis of power. The new traditionalism is the renewal of the traditional old schemes and methods of management. Neotraditionalist political practice in recent years has revealed a number of negative aspects in the political life of Russian society: the dominance of the party in power, the verticalization of power, the adaptation of power in the consolidation of society. The statement of modalities of neotraditionalism in the transformation of power as the system-forming Institute, predetermined the neo-conservative modernization, has been substantiated. The author of the study is convinced, that the inertial model of political development has been shown to the post-traditional transitional society, because it has been stipulated to the generational change of elites. In posttraditional society in the conditions of crisis the power, fighting against political turbulence, for the sake of achievement of political stability in society, applies not only mechanisms of political and legal regulation, but also neotraditionalist instruments of regulation. Therefore, there is a need to consider the problem of neotraditionalism not only in theoretical aspect, but also in practical terms. Political neotraditionalism is the extension of the sphere of informal relations. Neotraditionalism predetermined the specifics of the evolution of power and management in the context of country identification. Neotraditionalism in the management system of the modern information society is dual. Democratic of the personalized management models is relative. The modern information society has been prepared for the transition from a monosubject management model to a polysubject model. Neotraditionalism in the ontological sense is not the opposite of the old original traditionalism, which is confirmed by practice. Neotraditionalism in terms of negative stabilization passes a serious test on ethics.